Fatigue analysis to driver of intercity in West Sumatra Province, Indonesia a case study of Padang – Bukittinggi – Payakumbuh route - Ihsan, Taufiq; Arbi, Yaumal; Irawan, Andi; Sari, Intan Purnama (Universitas Negeri Padang, 2020)
Traffic accidents were common problems in the implementation of a transportation system, including in West Sumatra Province, Indonesia. Traffic accidents that occur every year were the evidence by the number of traffic accidents that occur every year. One of the causes of traffic violations that result in accidents is the risk of driver fatigue while working. This study analyzed the work-fatigue in the driver of the Intercity in Province bus (AKDP) the scope of this study was all AKDP bus drivers with the origin of Padang City, Bukittinggi City, and Payakumbuh City. Measurement and analysis of work-fatigue were using the reaction timer to light response. The results showed that increasing the number of shifts would increase driver fatigue. 33.33% of drivers run into medium level of fatigue, and 38.89% of drivers run into heavy level of fatigue. The relationship between work-fatigue and the driver's shift correlated very strongly and positively with a correlation value of r = 0.81. The owner of the company needs to take measures to improve management to minimize the level of work on this driver that has the potential to cause traffic accidents.